The Principles and Concepts of Natural Moral Theory in the Novel Sa.b.a! (Prinsip dan Konsep Teori Moral Alamiah dalam Novel Sa.b.a!) (Malay Literature, 2018)
This paper examines the principles and concepts of nature moral theory in the novel "Sa.b.a!", the works of Haji Abdul Aziz Tuah who is the recipient of the 2015 SEA Write Award for Brunei Darussalam, on its surface structure. The discussion in this paper is to express this novel in conformity with the principles and concepts of nature moral theory, which is meet the situation, events and processes of nature the creation of God. This study shows that the novel of the author's creation has occurred with God's blessing. Author, like other nature elements are capable of forming something that eventually becomes a source of nature as well. In this case the literary work (novel) that combines experience and knowledge into text becomes the source of nature the author's creation. Meanwhile narratives in novel can be likened as a dream that contains a mysterious event but there is experience and knowledge in it. The formation of this novel's text is like natural occurrence of nature that has diversity, balance and harmony. Its existence or creation is not futile but it contains usefulness in accordance with nature occurrence, beneficial and beautiful, as a lesson to human beings.Keywords: nature, creator, dream, object, narrative, surface